2006
DOI: 10.1111/j.1834-7819.2006.tb00415.x
|View full text |Cite
|
Sign up to set email alerts
|

Caries experience in preschool children referred for specialist dental care in hospital

Abstract: Background: Increasing numbers of preschool children are being referred for specialist dental management in a paediatric hospital. Most cases have severe early childhood caries and require comprehensive management under general anaesthesia. The present study investigated risk factors for disease presence at initial consultation. Methods: A convenience sample of 125 children under four years of age from the north Brisbane region were examined and caries experience recorded using dmft and dmfs indices. A selfadm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 24 publications
3
21
0
2
Order By: Relevance
“…The prevalence of dental caries is high in children from lower socioeconomic groups and are often poorly nourished and suffer delayed growth and development compared with their healthy peers 11 . In these populations, prenatal and perinatal malnutrition are often the causes of enamel hypoplasia, reduced salivary secretion and low buffering capacity 12 .…”
mentioning
confidence: 99%
“…The prevalence of dental caries is high in children from lower socioeconomic groups and are often poorly nourished and suffer delayed growth and development compared with their healthy peers 11 . In these populations, prenatal and perinatal malnutrition are often the causes of enamel hypoplasia, reduced salivary secretion and low buffering capacity 12 .…”
mentioning
confidence: 99%
“…According to the American Academy of Pediatric Dentistry the most probable explanation is early 'vertical' and 'horizontal' transmission of mutant streptococci among male children and mothers or close male relatives 31 . However, the recorded data is not consistent with respect to the impact of the total number of children in the family on the occurrence of the disease 32,33 . Analysis of ECC occurrence in preschool institutions and other environments has shown that the prevalence of ECC is twice lower among children in kindergarten, even though there is a greater possibility of transmission of mutant streptococci from one child to another within a group 29 .More severe forms of the disease were common among children who were not in kindergarten 29 , and the reason for this is the importance of regular consumption of meals 34 and intensive medical and educational work with children in preschool institutions, which includes not only teachers but dentists as well 29 .…”
Section: Impact Of Socioeconomic Factors On the Occurrence Of Eccmentioning
confidence: 77%
“…Američka akademija za dečju stomatologiju, kao najverovatniji razlog, navodi raniju "vertikalnu" i "horizontalnu" transmisiju mutantnog streptokoka između majke i muške dece, odnosno između bliskih srodnika muškog pola 31 . Međutim, podaci iz literature nisu konzi-stentni kada je u pitanju uticaj ukupnog broja dece u porodici na razvoj ovog oboljenja 32,33 . Analiza pojave KRD-a u predškolskim ustanovama i izvan njih ustanovila je dva puta manju prevalenciju kod dece koja borave u vrtiću i pored dokazane veće mogućnosti širenja mutantnog streptokoka sa jednog deteta na drugo u kolektivu 29 .…”
Section: Impact Of Socioeconomic Factors On the Occurrence Of Eccunclassified
See 2 more Smart Citations